2011
DOI: 10.1016/s0924-9338(11)73594-5
|View full text |Cite
|
Sign up to set email alerts
|

FC13-09 - Antidepressant tianeptine (TIA) action is based on the acceleration of serotonin turnover in the synapse: a hypothesis

Abstract: IntroductionNeurochemical mechanism of TIA action is not clear.AimTo develop possible mechanism of TIA action in patients with anxious depression (Uzbekov et al., 2006, 2009).ResultsIt was found twofold increase of platelet monoamine oxidase (MAO) activity in depressed patients and its significant decrease under TIA action.DiscussionSynapse is considered as a complex biological system (nerve ending + astrocytes). It is supposed that at normal conditions about 75% of serotonin released in synaptic cleft undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Additionally, chronic tianeptine administration prolonged the climbing time in the modified Porsolt test in adult offspring. The effect of tianeptine may be due to its complex action including the unique properties on the serotoninergic system, by increasing reuptake and accelerate of serotonin turnover in the synapse (Uzbekov 2009 ). Moreover, tianeptine may modulate the glutamatergic and GABAergic systems (McEwen et al 2010 ), which as we previously demonstrated are impaired in prenatally stressed animals (Sowa et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, chronic tianeptine administration prolonged the climbing time in the modified Porsolt test in adult offspring. The effect of tianeptine may be due to its complex action including the unique properties on the serotoninergic system, by increasing reuptake and accelerate of serotonin turnover in the synapse (Uzbekov 2009 ). Moreover, tianeptine may modulate the glutamatergic and GABAergic systems (McEwen et al 2010 ), which as we previously demonstrated are impaired in prenatally stressed animals (Sowa et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…An unsettled question was whether tianeptine treatment caused hypersecretion of catecholamines in the adrenal medulla, resulting in lethal hypertensive crisis, because tianeptine facilitates fast turnover of serotonin at synaptic cleft (Uzbekov, 2009). However, the results of two previous studies are not in compliance with this presumption.…”
Section: Discussionmentioning
confidence: 99%
“…While venlafaxine is a member of SNRIs (serotonin-noradrenalin reuptake inhibitors), tianeptine is an atypical antidepressant drug. In contrast to tricycle antidepressants and selective serotonin reuptake inhibitors (SSRIs), it has been suggested that tianeptine decreases serotonin's bioactivity and its accumulation in serotonergic synapses of the central nervous system by promoting serotonin reuptake, and normalizing serotonergic neurotransmission [ 35 , 36 ]. Venlafaxine, which has a mechanism of action opposite to that of tianeptine (i.e.…”
Section: Discussionmentioning
confidence: 99%